Corporate performance in concentrated sectors: comparative study at the salt sector in the state of Rio Grande do Norte - Valdevino, Rosângela Queiroz Souza; Moura, Heber José de; Matos, Fátima Regina Ney (Revista de Administração da UFSM, 2018)
In the current competitive environment, administrative and financial follow-ups are essential for establishing the necessary requirements for efficient decision making. Thus, the objective of this study was to compare the business performance of the salaried sector of Rio Grande do Norte in the period of 2010/2011, with mining and hospital services sectors that also present a high degree of concentration, according to classification based on the Concentration Ratio (CR) and Herfindahl-Hirschman (HH).The research was of quantitative nature applied in 33 saline companies of Rio Grande do Norte. For the treatment of the data, the multivariate cluster analysis technique was performed. Regarding the results, it was possible to identify that the saline sector was not net of 11,11%. It can be concluded that, due to the inelasticity of the saline sector, it has shown growth in the State.